2023
DOI: 10.3390/ceramics6030083
|View full text |Cite
|
Sign up to set email alerts
|

New Glasses in the PbCl2–PbO–B2O3 System: Structure and Optical Properties

Abstract: New oxychloride lead borate glasses in the xPbCl2–(50-0.5x)PbO–(50-0.5x)B2O3 system were synthesized with a maximum lead chloride content of 40 mol%. The characteristic temperatures and mechanical and optical properties were studied. The incorporation of lead chloride led to a significant expansion of the transparency range in the UV (up to 355 nm) and IR regions (up to 4710 nm). Decreases in the Vickers hardness, density, and glass transition temperature were the consequences of a change in the structure. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 60 publications
(102 reference statements)
1
0
0
Order By: Relevance
“…The Raman results align with the FTIR findings, where the fraction of BO 4 units (N 4 ) increased from 0.4765 to 0.4967 with the addition of 0.1 mol% CuO. The CuO acts as a network modifier, breaking B-O-B linkages and generating non-bridging oxygen bonds associated with BO 4 structures [46,47]. Additional mainor peaks reported previously be Meraa et al [48,49] can be observed and assigned to compositional change as follows: 600-700 cm −1 atributed to BO 3 bending vibrations, 700-800 cm −1 assigned to BO 3 symmetric stretches, 800-900 cm −1 assigned to BO 4 vibrations, and that below 500 cm −1 attributed to the Lead-oxygen lattice vibrations.…”
Section: Raman Analysissupporting
confidence: 85%
“…The Raman results align with the FTIR findings, where the fraction of BO 4 units (N 4 ) increased from 0.4765 to 0.4967 with the addition of 0.1 mol% CuO. The CuO acts as a network modifier, breaking B-O-B linkages and generating non-bridging oxygen bonds associated with BO 4 structures [46,47]. Additional mainor peaks reported previously be Meraa et al [48,49] can be observed and assigned to compositional change as follows: 600-700 cm −1 atributed to BO 3 bending vibrations, 700-800 cm −1 assigned to BO 3 symmetric stretches, 800-900 cm −1 assigned to BO 4 vibrations, and that below 500 cm −1 attributed to the Lead-oxygen lattice vibrations.…”
Section: Raman Analysissupporting
confidence: 85%